2016
DOI: 10.1515/hmbci-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Successful prevention of preeclampsia in a high-risk pregnancy using progestogen dydrogesterone: a clinical case

Abstract: The presented clinical example convincingly demonstrates the efficacy of dydrogesterone (30 mg) in the prevention of severe preeclampsia in a high-risk patient (early development of preeclampsia and preterm Cesarean section in her first pregnancy, arterial hypertension). This case suggests using dydrogesterone as an option to prevent preeclampsia, as previously shown in a prospective randomized study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…P4 is an essential hormone in the process of reproduction, and circulating P4 is significantly lower in PE women compared to controls [16]. There are pieces of evidence that early P4 treatment in ART improves the incidence and outcome of pre-eclampsia [50][51][52]. In addition, animal experiments also demonstrated that P4 could attenuate hypertension, improve inflammation, and boost fetal weight in a reduced uterine perfusion pressure rat model [16,17,53].…”
Section: Discussionmentioning
confidence: 99%
“…P4 is an essential hormone in the process of reproduction, and circulating P4 is significantly lower in PE women compared to controls [16]. There are pieces of evidence that early P4 treatment in ART improves the incidence and outcome of pre-eclampsia [50][51][52]. In addition, animal experiments also demonstrated that P4 could attenuate hypertension, improve inflammation, and boost fetal weight in a reduced uterine perfusion pressure rat model [16,17,53].…”
Section: Discussionmentioning
confidence: 99%
“…A favourable effect of dydrogesterone has also been reported for 30 mg dydrogesterone from early pregnancy until 37 th week of gestation in a high-risk woman for preeclampsia prevention [22].…”
Section: Prevention Of Preeclampsiamentioning
confidence: 75%
“…from early pregnancy until 37th weeks of gestation. The pregnancy was uneventful and delivery was done by repeat Csection at 39th weeks of gestation with a fetal weight of 3750 g and a length of 53 cm [22].…”
Section: Recent Data On Dydrogesterone and Preeclampsiamentioning
confidence: 99%